Electrodynamics of Bechgaard Salts: Optical Properties of One-Dimensional Metals. (24th September 2012) - Dressel, Martin
Abstract : The electrodynamic properties of the quasi-one-dimensional organic conductors (TMTSF)2 X are discussed, with particular emphasis on important deviations from the simple Drude model, the transition from a Luttinger-liquid to a Fermi-liquid behavior at the dimensional crossover when pressure is applied or temperature reduced, indications of a pseudogap as well as a low-frequency collective mode. Superconductivity and spin-density-wave ground states breaking the symmetry and gaps should occur in the excitation spectra. The previous literature is summarized and the current status of our understanding presented. Novel THz experiments on (TMTSF)2 PF6 and (TMTSF)2 ClO4 not only shine light into some of the open questions, but also pose new ones.